2021
DOI: 10.1007/s43545-021-00151-4
|View full text |Cite
|
Sign up to set email alerts
|

Political marketing and social media influence on young voters in Ghana

Abstract: As the political and media landscape becomes more complex, political parties and candidates worldwide are continually exploring new ways and ideas to effectively communicate their messages to their target audience. Throughout the political history of Ghana, the mass media has played an integral role in political marketing successes. However, with the advent of the digital economy, social media platforms have unfolded new possibilities for politicians to engage with citizens. The study examined the extent to wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The findings demonstrated that political message propagation on social media has a favorable and significant association with young voters' political participation, political awareness, and political efficacy. Overall, the data suggested that the usage of social media could improve political engagement, particularly among young voters (Gogoi, 2020;Dankwah et al, 2021). Online political efficacy is proposed as a mechanism relating social media use and political participation in this article.…”
Section: Political Efficacy and Mediamentioning
confidence: 77%
“…The findings demonstrated that political message propagation on social media has a favorable and significant association with young voters' political participation, political awareness, and political efficacy. Overall, the data suggested that the usage of social media could improve political engagement, particularly among young voters (Gogoi, 2020;Dankwah et al, 2021). Online political efficacy is proposed as a mechanism relating social media use and political participation in this article.…”
Section: Political Efficacy and Mediamentioning
confidence: 77%